Redes de cooperação versus custos de transação: um estudo de caso da Associação Gaúcha de Empreendimentos Lácteos (AGEL) na mesorregião noroeste do Rio Grande do Sul - Peroni, Neimar Damian (2009)
The purpose of this work is to contribute for the management of a small dairy producers network of cooperation throughout a structure of governance definition, which mitigates transaction costs in the dairy products market in the northeast of Rio Grande do Sul State. According to theoretical aspect, this research utilized the Transaction Costs Economy, and the New Institutional Economy. Sixteen cooperative companies, and an association of producers formed the network less than a year ago. One of its main goals is to make investments in a transaction costs. The methodology was the case study with only one unit of analysis. To main suggestion from this study was that the network could make use of different structures of governance for each phase described in its planning, beginning by market s shape, evolving to the hybrid shape, until it reaches the hierarch or integration shape according to performed investments in specific assets for the milk processing in natura. Complementary to the indication of structures of governance we presented other strategies to the network s logistics, such as: applying of Supply Chain Management to choose commercial partners as well as to reach the Modern Industrial Organization to accomplish a unique image, to find competitive strategies for the products of the AGEL.